The Effect of Guided Inquiry Learning Model Implementation Assisted by the Phyphox Application on Science Process Skills and Learning Interest in Collision Topics - Amrullah, Muhammad Fajri; Suyatna, Agus; Wicaksono, Blasius Anggit; Abdurrahman, Abdurrahman (Department of Physics Education, Universitas Mataram, 2025)
This research aims to determine the effect of implementing the Guided Inquiry learning model assisted by the Phyphox application on Science Process Skills (SPS) and Learning Interest in the topic of Collisions. The research was conducted at SMAN 1 Banjar Agung using a pre-experimental method with a one-group pre-test - post-test design. The sample used was class XI.5 as the experimental class. The instruments used included essay questions to measure SPS and a closed-ended questionnaire with a Likert scale to assess Learning Interest.This research employed Normality Test, N-Gain Test, and Paired Sample T-Test to determine the improvement in students' SPS and Learning Interest. The results showed that the implementation of the Guided Inquiry learning model assisted by the Phyphox application had an effect on improving students' Science Process Skills and Learning Interest. This was indicated by the N-Gain values from the pre-test – post-test results and the learning interest questionnaire in the experimental class, which were 0.598 and 0.525, respectively. Furthermore, this was supported by the Paired Sample T-Test results, which showed a Sig. (2-tailed) value of 0.000 < 0.05 for the overall data.Thus, the Guided Inquiry learning model assisted by the Phyphox application is effective in enhancing students' Science Process Skills and Learning Interest.